PENINGKATAN KEMAMPUAN PEMAHAMAN MATEMATIS MELALUI PEMBELAJARAN DENGAN STRATEGI THINK TALK WRITE (TTW) DI SEKOLAH DASAR - Siti Quratul Ain; Eva Astuti Mulyani (Tunjuk Ajar: Jurnal Penelitian Ilmu Pendidikan, 2018)
This study aims to examine improving students' mathematical understanding through Think Talk Write learning strategy. The method is a quasi-experiment with experimental class research design and the pretest-posttest control class. The experimental class implemented the Think Talk Write learning strategy and the control class by direct learning model. The population of this study is a fourth-grader of one elementary school in Bandung. The sample in this research is 50 students, two classes. The instrument used in data collection is a test of the mathematical understanding ability of the description form. The result data were N-gain score analyzed by using independent-test t-test and Mann-Whitney test. From this research, I obtained the conclusion, improving students’ mathematical understanding ability who get learning with Think Talk Write strategy is better than students who gain learning by direct learning.